Cerebrovascular effects of glibenclamide investigated using high-resolution magnetic resonance imaging in healthy volunteers. Issue 6 (June 2021) - Al-Karagholi, Mohammad Al-Mahdi; Ghanizada, Hashmat; Nielsen, Cherie Amalie Waldorff; Ansari, Assan; Gram, Christian; Younis, Samaria; Vestergaard, Mark B; Larsson, Henrik BW; Skovgaard, Lene Theil; Amin, Faisal Mohammad; Ashina, Messoud
Glibenclamide inhibits sulfonylurea receptor (SUR), which regulates several ion channels including SUR1-transient receptor potential melastatin 4 (SUR1-TRPM4) channel and ATP-sensitive potassium (KATP ) channel. Stroke upregulates SURl-TRPM4 channel, which causes a rapid edema formation and brain swelling. Glibenclamide may antagonize the formation of cerebral edema during stroke. Preclinical studies showed that glibenclamide inhibits KATP channel-induced vasodilation without altering the basal vascular tone. The in vivo human cerebrovascular effects of glibenclamide have not previously been investigated. In a randomized, double-blind, placebo-controlled, three-way cross-over study, we used advanced 3 T MRI methods to investigate the effects of glibenclamide and KATP channel opener levcromakalim on mean global cerebral blood flow (CBF) and intra- and extracranial artery circumferences in 15 healthy volunteers. Glibenclamide administration did not alter the mean global CBF and the basal vascular tone. Following levcromakalim infusion, we observed a 14% increase of the mean global CBF and an 8% increase of middle cerebral artery (MCA) circumference, and glibenclamide did not attenuate levcromakalim-induced vascular changes. Collectively, the findings demonstrate the vital role of KATP channels in cerebrovascular hemodynamic and indicate that glibenclamide does not inhibit the protective effects of KATP channel activation during hypoxia and ischemia-induced brain injury.